PENGARUH PERSEPSI KEBERMANFAATAN, PERSEPSI KEMUDAHAN PENGGUNAAN, DAN KEPUASAN WAJIB PAJAK TERHADAP PENGGUNAAN EFILLING BAGI WAJIB PAJAK ORANG PRIBADI - Junawan (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2018)
The aims of this research is to determine how much influence perception of usefullness, perception of ease of use and taxpayer satisfaction of the use of e-filling on employees PT. Accentuates Medan. This research is an associative research. The type of data used is the primary data obtained by distributing questionnaires to respondent on employees PT. Accentuates Medan who have used e-filling of 50 respondent. Data collection techniques in this study through quesionnaries and observations. The author uses multiple linear analysis techniques with SPSS IBM software to process the data, first to test the data. The result of the research shows that the perception of usefulness has a positive and significant effect on the use of e-filling. Perceived ease of use has no positive and significant effect on the use of efilling, and perception of user satisfaction have a positive and significant effect on the use of e-filling. However, perceptions of usability, perception of ease of use and user satisfaction simultaneously have a positive and significant influence on the use of e-filling.